Effects of Roasted Schisandra Chinensis (Turcz.) Baill and Lycium Chinense Mill. and Their Combinational Extracts on Antioxidant and Anti-Inflammatory Activities in RAW 264.7 Cells and in Alcohol-Induced Liver Damage Mice Model. (17th September 2021) - Kim, Ha-Rim; Kim, Sol; Kim, Seon-Young
Abstract : Schisandra chinensis (Turcz.) Baill (SC) and Lycium chinense Mill. (LC) are widely distributed in Asia, where the fruit has traditionally been used for medicinal herbs. We previously reported that the roasting process improved the antioxidant and their hangover relieving effects. In this study, we assessed the antioxidant and anti-inflammatory effects of water extract of SC, LC, and a mass ratio 1 : 1 mixture (SL), after roasting in RAW264.7 macrophage cells stimulated with lipopolysaccharide (LPS). Roasted SL (RSL) extracts showed greater enhancement potential than the others, based on the inhibition of NO (nitric oxide) and intracellular reactive oxygen species (ROS) production in RAW264.7 cells. RSL also significantly decreased the proinflammatory markers (e.g., iNOS, COX-2, TNF- α, and IL-1 β ) and NAD(P)H oxidase (NOX) signaling proteins (i.e., NOX (−1, −2, and −4), p22 phox, p47 phox, and p67 phox ). The inflammatory cytokine, tumor necrosis factor-alpha, interferon-1 beta levels, NF-kB, and mitogen-activated kinase activations were also significantly inhibited by RSL treatment. Based on the results of cellular levels, we compared the promotion effects of RSL extract on liver injury mediated by alcohol-induced inflammation and oxidative stress in mice. Mice were fed a Lieber–DeCarli regular liquid alcohol diet with or without SL and RSL extracts for six weeks. Alcohol intake caused liver injury, evidenced by an increase in serum alanine aminotransferase and aspartate aminotransferase activities. Consistent with the results in cell levels, RSL treatment remarkably downregulated ROS and inflammatory factors, as well as their signaling molecules, in serum and tissues. These results suggest that the roasting of SC and LC could potentially elevate the inhibition effect on alcohol-induced inflammation and oxidative stress and consequently prevent alcoholic liver damage. Also, the combination of SC and LC may provide a more synergistic effect than either alone.